Pendampingan Pengurusan Izin Edar BPOM Produk Jamu Gendong Desa Ngablak, Kecamatan Dander, Kabupaten Bojonegoro - Setyaningrum, Dyah; Maghfiroh, Amalia Ma’rifatul (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
The main idea of this activity was to provide information for the business actors of jamu gendong to be able to administer product permits at BPOM. This effort was carried out by providing skills and insight to the business actors of jamu gendong through socialization, counseling, and joint training with related agencies. This training was carried out from the selection of simplisia to business management. The result of this activity was that the partner could produce the products of jamu gendong that had the better quality in terms of product safety so that the products of jamu gendong from Ngablak Village could be marketed in supermarkets, gift shops or through online. In addition, jamu gendong was expected to become the main beverage as asubstitute for mineral water in the meetings at Village Meeting Hall of Ngablak. The permit from BPOM was expected to influence the improvement of the welfare of the members of the community.